Instrumentos de gestión aplicados para el desarrollo inmobiliario y la regulación del colegio La Presentacion San Fasón en el centro de Bogotá (2019)
This exercise accounts for the instrument used and its application in their respective properties, highlighting the participation in goodwill being the most common instrument in the execution of real estate developments through the PRM. With the results obtained, some real estate development simulations were carried out based on the current norm, established by the District Planning Secretariat, with which the most convenient way can be identified so that the Hermanas de la Caridad Dominicas de la Presentación can give you a greater use of the property through real estate development, established under the appropriate planning instrument.